Coral Diversity at Losin Pinnacle, an Offshore Reef in the Gulf of Thailand: Toward a Future MPA - Yucharoen, Mathinee; Chankong, Anchalee; Phongsuwan, Niphon; Ninwat, Santi; Darumas, Udomsak; Thongkao, Suthira; Phasombun, Supaporn (Frontiers in Marine Science, 2020)
Severe coral bleaching events in the Gulf of Thailand and the Andaman Sea coast of Thailand had caused widespread coral mortality in 1998 and 2010. Consequently, the decrease in coral populations impacted the structure, health, and services of Thai coral reefs. However, most colonies in the offshore reef of Losin were still alive after the coral bleaching events. Therefore, this study was conducted by the Department of Marine and Coastal Resources in order to help to establish a proposal for a Marine Protected Area (MPA). Surveys on coral diversity were conducted to produce a checklist of reef building corals. Seventy-six coral species were found, with the most dominant species being Porites lutea and Acropora communities, such as A. intermedia, A. grandis, A. muricata, A. cytherea, and A. valenciennesi. This area is expected to be designated as a restricted MPA area, under the “Act on the Promotion of Marine and Coastal Resources Management B.E. 2558 (2015)”. The high diversity of hard corals discovered in this study assist in promoting the inclusion of Announcement of the Losin Marine and Coastal Resources Protected Areas following the Ministerial Regulation.